Primary Hepatic Mucosa-Associated Lymphoid Tissue Lymphoma: A Case Report - Kyung Su Kwag; Suk Ki Jang; Jae Woo Yeon; So Ya Paik; Sang Jong Park; Hyuk Jung Kim (대한영상의학회지, 2016)
Primary hepatic mucosa-associated lymphoid tissue (MALT) lymphoma is an extremely rare lesion. Primary hepatic lymphomas are known to present as a single mass in > 70% of cases, and in many instances with no specific features on imaging. Herein, we described a case of primary hepatic MALT lymphoma in a 71-year-old woman. A computed tomography (CT) scan revealed a mass, 4.5 × 3.0 cm, in liver segment 2 (S2) that was poorly defined, with subtle enhancement during the arterial phase. Gadoxetic acid-enhanced magnetic resonance imaging also showed an arterially enhancing mass in S2, with low signal intensity during the hepatobiliary phase and high signal intensity on diffusion-weighted imaging with a high b-value. On fluorodeoxyglucose positron emission tomography/CT imaging, the mass showed a high standardized uptake value. Ultrasonography (US) revealed a hypoechoic mass, and US-guided core needle biopsy confirmed a hepatic MALT lymphoma.